(3OhQ GdSjGMI aj GdJfejI GdGLJeGYjI (B:s (3OQGSI JbhjejI ddbQi GdSjGMjI (B/s - (3GHQGgje, haGA Rcjs ((3GdGScfOQjI(B: s (3GdecJH GdLGeYj GdMOjK(B, s, 2006)
(3GdfXQjI (B- (3GdfTCI (B- (3Gdeaghe h GdSjGMI h CfhGYgG h CgejJgG GVGaI Gdi GdJTQjYGJ h GdbhGfjf h YdGbJgeG HJWhQ XGgQI GdSjGMI h GdJfejI GdSjGMjI h CNjQG NGJeI GdOQGSI h Cge GdfJGFL h GdJhUjGJ(B.s
(3eQGLY U(B.456, (3edGMb U(B.473s
Keywords: (3GdJfejI GdGLJeGYjIs; (3GdJfejI GdSjGMjIs; (3GdSjGMIs